2013
DOI: 10.1117/1.jei.22.3.033025
|View full text |Cite
|
Sign up to set email alerts
|

Stereo one-shot six-band camera system for accurate color reproduction

Abstract: Abstract. For accurate color reproduction of motion pictures or still pictures of moving objects, we developed a different one-shot sixband image-capturing and visualization system that combines multiband and stereo imaging techniques. The proposed system consists of two consumer-model digital cameras and an interference filter whose spectral transmittance is comb-shaped. Subpixel correspondence search between the stereo image pairs is conducted and image transformation whose parameters are estimated from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…A solution method for reliably capturing dynamic natural scenes is to construct a one-shot multi-band imaging system. In practice, the system can be constructed using a stereo system [31,32] or multispectral filter array [33,34]. However, these proposed multiband imaging systems are neither omnidirectional nor HDR.…”
Section: Introductionmentioning
confidence: 99%
“…A solution method for reliably capturing dynamic natural scenes is to construct a one-shot multi-band imaging system. In practice, the system can be constructed using a stereo system [31,32] or multispectral filter array [33,34]. However, these proposed multiband imaging systems are neither omnidirectional nor HDR.…”
Section: Introductionmentioning
confidence: 99%
“…As discussed in explanations of Figure 15, increasing the gain in order to reduce the exposure time also results in a decreased exposure, and thus, a drop in SNR. On the other hand, sensor alignment and demosaicing in multi-sensor cameras are notoriously hard tasks that if not treated, they affect the image quality [15,56]. Studying the impact of these spatial factors is not possible with color patches or simulated images.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of color reproduction accuracy with other systems is not easy because there are few studies to show the comprehensive evaluation of the total color image production including both the camera and display devices . We have found that the current color reproduction performances in the three projection systems are roughly comparable with a real‐time video system using six‐band HDTV camera and six‐primary display…”
Section: Algorithm To Design Practical Illuminantsmentioning
confidence: 95%